Fuel Dispensing Monitoring System - -, Aremu Oluyomi Olugboyega (2008)
An information system aimed at monitoring fuel dispensing is designed using php and JavaScript with MySQL as the database. It collects the supply and sales patterns of fuel types in filling station.